3D Microenvironment Stiffness Regulates Tumor Spheroid Growth and Mechanics via p21 and ROCK. Issue 9 (24th July 2019) - Taubenberger, Anna V.; Girardo, Salvatore; Träber, Nicole; Fischer‐Friedrich, Elisabeth; Kräter, Martin; Wagner, Katrin; Kurth, Thomas; Richter, Isabel; Haller, Barbara; Binner, Marcus; Hahn, Dominik; Freudenberg, Uwe; et al.
Abstract: The mechanical properties of cancer cells and their microenvironment contribute to breast cancer progression. While mechanosensing has been extensively studied using 2D substrates, much less is known about it in a physiologically more relevant 3D context. Here it is demonstrated that breast cancer tumor spheroids, growing in 3D polyethylene glycol‐heparin hydrogels, are sensitive to their environment stiffness. During tumor spheroid growth, compressive stresses of up to 2 kPa build up, as quantitated using elastic polymer beads as stress sensors. Atomic force microscopy reveals that tumor spheroid stiffness increases with hydrogel stiffness. Also, constituent cell stiffness increases in a Rho associated kinase (ROCK)‐ and F‐actin‐dependent manner. Increased hydrogel stiffness correlated with attenuated tumor spheroid growth, a higher proportion of cells in G0/G1 phase, and elevated levels of the cyclin‐dependent kinase inhibitor p21. Drug‐mediated ROCK inhibition not only reverses cell stiffening upon culture in stiff hydrogels but also increases tumor spheroid growth. Taken together, a mechanism by which the growth of a tumor spheroid can be regulated via cytoskeleton rearrangements in response to its mechanoenvironment is revealed here. Thus, the findings contribute to a better understanding of how cancer cells react to compressive stress when growing under confinement in stiff environments. Abstract : The interrelationship between tumor spheroid mechanics, growth, and microenvironment stiffness is explored using a 3D in vitro model. Increasing microenvironment stiffness causes compressive stress on breast cancer spheroids, alters cytoskeleton organization, increases constituent cell stiffness via ROCK, and slows down cell cycle progression via p21. Thus, the findings provide insights into how cells adapt their proliferation when grown under confinement.